TEACHERS‟ LEVEL OF KNOWLEDGE, CAUSES, EFFECTS AND SAFETY MEASURES OF COVID-19 PANDEMIC IN ABAKALIKI EDUCATION ZONE OF EBONYI STATE, NIGERIA - Mercy IfunanyaAni; David OnyemaechiEkeh; Chinyere O. Elom; Beatrice A. Eze; Peter ChikaUzosike; David AgwuUdu; MfonEdet Thompson; Abigail ChikodinakaObodo; Claris NnennaEze (International Journal of Psychosocial Rehabilitation, 2020)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered corona virus. Covid-19 disease, originated from Wuhan, Hubei Province, China in December 2019. The World Health Organization (WHO) has declared the COVID-19 pandemic a global health emergency. The purpose of the study was to determine teachers’ level of knowledge on the causes, effects and safety measures of COVID 19 pandemic in Abakaliki, Ebonyi State Nigeria. Descriptive research design was adopted for the study. Three research questions guided the study while three null hypotheses were formulated and tested at 0.05 level of significance. Purposive sampling technique was used to select 150 teachers comprising of 30 male and 120 female secondary school teachers in Abakaliki, Ebonyi State of Nigeria. Researchers’ self-developed questionnaire titled “Teachers’ level of knowledge on the causes, effects and safety measures of COVID 19 pandemic questionnaire” was used for datacollection. Data collected were analyzed using percentage to answer the research questions. The results of data analysis showed that teachers had moderate level of knowledge in the causes (62% for males and 68% for females), effects (73% for males and 81% for females) and safety measures (74% for males and 87% for females) of COVID-19 pandemic. Conclusion and recommendations were made based on the findings of the study.